2020
DOI: 10.1097/mat.0000000000000971
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil to Lymphocyte Ratio Is Related to Thrombotic Complications and Survival in Continuous Flow Left Ventricular Assist Devices

Abstract: Left ventricular assist devices (LVADs) have become an established treatment for advanced heart failure, although with long-term support these patients are potentially exposed to serious complications. Our purpose was to assess the role of the neutrophil to lymphocyte ratio (NLR) in LVAD complications and to evaluate if higher values of NLR after 4–6 months on LVAD support (NLR 4_6m) are associated with worse prognosis. All consecutive patients who received a HeartWare LVAD (N = 188, age 50 ± 13 years), as bri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…Another longitudinal analysis of NLR in patients with advanced HF receiving LVAD therapy as bridge to transplant, carried out by Ferrera et al, confirmed the rise and fall in NLR levels immediately after and several months after surgery [46]. Patients with NLR higher than median during the 4-6 months follow-up had higher rates of stroke and mortality [46].…”
Section: Left Ventricular Assist Devicementioning
confidence: 85%
See 1 more Smart Citation
“…Another longitudinal analysis of NLR in patients with advanced HF receiving LVAD therapy as bridge to transplant, carried out by Ferrera et al, confirmed the rise and fall in NLR levels immediately after and several months after surgery [46]. Patients with NLR higher than median during the 4-6 months follow-up had higher rates of stroke and mortality [46].…”
Section: Left Ventricular Assist Devicementioning
confidence: 85%
“…Patients with NLR higher than median during the 4-6 months follow-up had higher rates of stroke and mortality [46]. NLR during follow-up higher than 4.4 was an independent predictor of mortality, associating significantly shorter survival time [46].…”
Section: Left Ventricular Assist Devicementioning
confidence: 94%
“…We have shown that the neutrophil to lymphocyte ratio as a marker of inflammation predicted adverse outcomes including strokes and mortality. 24 Likewise, Batra et al have shown that preimplant CRP levels predicted mortality, right ventricular failure, and stroke. 25…”
Section: Cte and Infection Cte But Never Infection Pmentioning
confidence: 99%
“…Nevertheless, inflammation not related to infection though associated with chronic disease may be thrombogenic. We have shown that the neutrophil‐to‐lymphocyte ratio as a marker of inflammation predicted adverse outcomes 5 …”
Section: Relationship Between Infection and Thrombotic Eventsmentioning
confidence: 98%
“…We have shown that the neutrophil-to-lymphocyte ratio as a marker of inflammation predicted adverse outcomes. 5…”
Section: Infection and Thrombotic Eventsmentioning
confidence: 99%